Analisis Faktor Faktor Tinggihnya Kasus Stunting pada Balita Desa Sido Sari Kabupaten Seluma - Hesti Rahma Juliana; Iin Larasati; Jelly Furnama Sari; Rangga Darma Gunawan; Zuliha Nuramin Nanti; Ismail Ismail (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Stunting is still a nutritional problem in Indonesia that has not been resolved. Stunting is a physical growth disorder characterized by a decrease in growth rate and is the impact of nutritional imbalance. This research aims to describe several factors that trigger the high number of stunting cases among toddlers that occur in Sido Sari Village, Seluma Regency. The method used in the research is qualitative descriptive research where research data is obtained from the results of in-depth interviews and field observations as well as documentation of all research stakeholders. The results of this research show that there are several factors that trigger the high number of stunting cases among toddlers in Sido Sari Village, including lack of education of parents of toddlers, economic limitations and lack of training and skills of village health cadres.